The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.lindif.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Can reading fluency and self-efficacy of reading fluency be enhanced with an intervention targeting the sources of self-efficacy?

Abstract: Can reading fluency and self-efficacy of reading fluency be enhanced with an intervention targeting the sources of self-efficacy?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…Classmate controls were matched for gender (when possible), and they received business-as-usual support, including special education usually provided in the school. The reading intervention group consisted of children with reading fluency deficits who received the intervention as part of the SELDI project in small groups during the same period ( N = 85; for details, see Aro et al, in press ).…”
Section: Methodsmentioning
confidence: 99%
“…Classmate controls were matched for gender (when possible), and they received business-as-usual support, including special education usually provided in the school. The reading intervention group consisted of children with reading fluency deficits who received the intervention as part of the SELDI project in small groups during the same period ( N = 85; for details, see Aro et al, in press ).…”
Section: Methodsmentioning
confidence: 99%
“…A plenty of studies were piloted to examine the connection among self-efficacy beliefs and reading comprehension. Majority of the researchers considered primary school students as their study's sample (Aro et al 2018 ). All of the abovementioned studies found significant association between self-efficacy beliefs and reading comprehension except on study (i.e., Booth et al, 2017), which found an insignificant relationship.…”
Section: Self-efficacy Beliefs and Reading Comprehensionmentioning
confidence: 99%
“…Studies conducted regarding the relationship between self-efficacy sources and self-efficacy beliefs in English skills are limited. Aro et al (2018) conducted an intervention study in which they introduced selfefficacy sources as an intervention. The results indicated that self-efficacy sources significantly influenced reading self-efficacy beliefs.…”
Section: Self-efficacy Beliefs and Its Sourcesmentioning
confidence: 99%
“…In the EFL/ESL context, several studies focused on the research regarding self-efficacy beliefs in all the four skills of English language. For instance, several studies are on listening self-efficacy (i.e., Rahimirad & Zare-ee, 2015;Taguchi, 2018;Todaka, 2017), on speaking self-efficacy (i.e., Idrus & Salleh, 2017;Kamaruddin & Zawawi, 2017), on reading self-efficacy (i.e., Aro et al, 2018;McLean & Poulshock, 2018), and on writing self-efficacy (i.e., Ekholm, Zumbrunn, & Bandura (1997) defines self-efficacy beliefs as persons' perceptions regarding his capabilities to carry out particular actions. Self-efficacy beliefs denote persons' subjective anticipations of and devotion to achieve the academic tasks at hand (Lau & Roeser, 2002).…”
Section: Introductionmentioning
confidence: 99%